Biochar manure decreases ammonia volatilization loss and sustains crop productivity in rice paddy - Canatoy, Ronley C.; Cho, Song Rae; Galgo, Snowie Jane C.; Park, So Yeong; Kim, Pil Joo (Frontiers in Environmental Science, 2024)
Manure application has been recommended to improve soil quality and mitigate global warming via soil carbon (C) sequestration. However, its application can significantly increase ammonia (NH3) volatilization loss, causing secondary environmental problems such as acidification, eutrophication, and particulate matter formation. To investigate the potential of stabilized manure amendments in reducing NH3 emissions in flooded rice paddies, three types of swine manure amendments (fresh, composted, and biochar) were applied at a rate of 12 Mg ha -1 (dry weight) under standard fertilization (N-P2O5-K2O=90-45-57 kg ha -1 ). NH3 emission was characterized using the static chamber method. Regardless of manure management practices, NH3 fluxes increased significantly right after the application of inorganic nitrogen (N) fertilizer (urea). The whole manure was applied as the basal fertilizer before rice transplanting, but NH3 emission rates increased more dramatically following urea application in manure treatments. Fresh and composted manure applications significantly increased seasonal NH3 volatilization loss compared to the control, but biochar did not. Compost manure significantly increased rice grain productivity due to higher N content, while fresh and biochar manures did not increase rice productivity because of fewer panicles per hill and fewer grains per panicle. Consequently, biochar resulted in lower NH3 intensity, meaning seasonal NH3 flux per grain yield, whereas fresh and compost manures substantially increased this intensity. Therefore, biochar manure might be a more reasonable organic amendment than fresh and composted manures for reducing NH3 emission impacts in rice paddies.